1992
DOI: 10.1007/bf00229004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and histopathological changes following permanent bilateral carotid artery ligation in Wistar rats

Abstract: Cerebral blood flow and histopathological changes after bilateral carotid artery ligation (BCAL) in Wistar rats were studied. Eight of the 38 rats (21%) died within one week. In the 30 survivors, the incidence of histopathological change was 90% in the caudate nucleus, 23% in the cortex, 30% in the hippocampus, and 0% in the other structures. Local cerebral blood flow (LCBF) was measured using the quantitative autoradiographic 14C-iodoantipyrine technique in 24 anatomically discrete regions of the brain. BCAL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 18 publications
7
76
0
1
Order By: Relevance
“…Animal models offer a good possibility to reveal the potential underlying mechanisms that link reduced CBF and the decaying capillary condition in the brain. For example, the permanent ligation of both common carotid arteries of rats (two vessel occlusion, 2VO) was developed as a model of chronic cerebral hypoperfusion, where the blood supply to the brain is reduced to about 70% of the original rate [54]. This agrees with the drop in CBF in the hippocampus and temporal cortex of AD patients [13,41].…”
Section: Reduced Cbf and Cerebral Capillary Ultrastructurementioning
confidence: 85%
“…Animal models offer a good possibility to reveal the potential underlying mechanisms that link reduced CBF and the decaying capillary condition in the brain. For example, the permanent ligation of both common carotid arteries of rats (two vessel occlusion, 2VO) was developed as a model of chronic cerebral hypoperfusion, where the blood supply to the brain is reduced to about 70% of the original rate [54]. This agrees with the drop in CBF in the hippocampus and temporal cortex of AD patients [13,41].…”
Section: Reduced Cbf and Cerebral Capillary Ultrastructurementioning
confidence: 85%
“…14,21,22 Our previous studies revealed that the WM is preferentially damaged in these rats with an increase in reactive astroglia and activated microglia and that WM lesions are found mostly in the optic nerve and optic tract and to a lesser extent in the medial part of the corpus callosum, anterior commissure, internal capsule, and caudoputamen. 10 -14 Furthermore, these animals are cognitively impaired in the Morris water maze and radial maze tasks.…”
Section: Miyamoto Et Al Neuronal Damage By Hypocapnia During Anesthesmentioning
confidence: 90%
“…The neuronal damage occurs in the gray matter, including the hippocampus, the cerebral cortex, the caudoputamen, and the ventrolateral part of the thalamus in association with reactive astrogliosis and activation of microglia in the same regions. 36 -40 Conversely, the gray matter lesions in chronic cerebral hypoperfusion are mild or scarce, 10,21,41 suggesting that regional tissue vulnerability depends on the mode of ischemic insult. Therefore, additional gray matter damage after hypocapnia, as evidenced by the loss of MAP immunoreactivity in the caudoputamen and the cerebral cortex, may indicate an overlay of acute ischemic insult onto chronic ischemic damage.…”
Section: Miyamoto Et Al Neuronal Damage By Hypocapnia During Anesthesmentioning
confidence: 99%
“…Chronic encephalic hypoxemia in rats can be achieved by permanent bilateral carotid ligation (PBCL), which generates chronic moderate hypoglycemia that is associated with ageing and dementia, besides neurocognitive impairment and systemic reactions such as sympathetic nervous system reactions, immune cellular suppression, and opportunity for spontaneous bacterial infections [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%